2001
DOI: 10.1111/j.1755-6686.2001.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Job‐related stress among nursing personnel in Greek dialysis units

Abstract: The purpose of this study was to describe specific work-related factors that contribute to increased levels of stress experienced by nursing personnel, and to compare their impact on nurses and assistant nurses who work in Dialysis Units (DU) to those who work in Peritoneal Dialysis Units (PDU) in Greece. The sample of the study consisted of 682 members of nursing personnel working in DU and in PDU in Greek Hospitals. The collection of data was done by means of a questionnaire. The latter included questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 8 publications
1
61
0
3
Order By: Relevance
“…Work in dialysis facilities is marked by intensive and long-term contact with chronically ill patients [1,2], who are frequently frustrated or depressive [3]. This confrontation with suffering and death is very demanding for the medical care personnel in dialysis facilities [2,4-6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in dialysis facilities is marked by intensive and long-term contact with chronically ill patients [1,2], who are frequently frustrated or depressive [3]. This confrontation with suffering and death is very demanding for the medical care personnel in dialysis facilities [2,4-6].…”
Section: Introductionmentioning
confidence: 99%
“…Current scientific knowledge indicates that there are positive aspects of this work, including high job satisfaction [1,7]. Moreover, nurses in dialysis facilities perceived their work as worthwhile and were very interested in professional details [17].…”
Section: Introductionmentioning
confidence: 99%
“…The death of patients following long-term care can also lead to burnout in dialysis unit personnel. 16,17 A literature search revealed that the exhaustion levels of physicians, teachers, nurses from various clinics and academics have been studied in Turkey. 9,13,18 However, there are few studies that focus on fatigue and burnout in dialysis unit nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Stresas, kaip kenksmingas darbo aplinkos veiksnys, būdin-gas hemodializės skyriaus medicinos darbuotojams, nes jų veiklai būdinga didelė profesinė ir socialinė atsakomybė, sudėtingų užduočių sprendimas, dideli krūviai, laiko trū-kumas, konfliktinės situacijos ir kiti stresoriai [14,15].…”
Section: Hemodializės Skyriuje Dirbančių Medicinosunclassified